Dog Urine Has Acute Impacts on Soil Chemistry in Urban Greenspaces - Allen, John A.; Setälä, Heikki; Kotze, David Johan (Frontiers in Ecology and Evolution, 2020)
Urban residents and their pets utilize urban greenspaces daily. As urban dog ownership rates increase globally, urban greenspaces are under mounting pressure even as the benefits and services they provide become more important. The urine of dogs is high in nitrogen (N) and may represent a significant portion of the annual urban N load. We examined the spatial distribution and impact of N deposition from dog urine on soils in three urban greenspace typologies in Finland: Parks, Tree Alleys and Remnant Forests. We analyzed soil from around trees, lampposts and lawn areas near walking paths, and compared these to soils from lawn areas 8 m away from pathways. Soil nitrate, ammonium, total N concentrations and electrical conductivity were significantly higher and soil pH significantly lower near path-side trees and poles relative to the 8 m lawn plots. Also, stable isotope analysis indicates that the primary source of path-side N are distinct from those of the 8 m lawn plots, supporting our hypothesis that dogs are a significant source of N in urban greenspaces, but that this deposition occurs in a restricted zone associated with walking paths. Additionally, we found that Remnant Forests were the least impacted of the three typologies analyzed. We recommend that landscape planners acknowledge this impact, and design parks to reduce or isolate this source of N from the wider environment.